Challenges in Implementing Islamic Pre-Marital Guidance: A Qualitative Study - Amirah, Nabilla; Afrizal, Jhon; Walidain, Ridal; Layla, Desteny (Jurnal Elsyakhshi, 2025)
To encourage the formation of strong and harmonious families (sakinah, mawaddah, warahmah), the Directorate General of Islamic Community Guidance issued Decree No. 379 of 2018 on Pre-Marital Guidance for prospective brides and grooms. However, despite the launch of this initiative, divorce rates in West Sumatra continue to rise, raising concerns about the effectiveness of its implementation. This field study employs observational methods, interviews, and documentation, analyzed through a descriptive qualitative approach. The findings reveal several challenges faced by the Religious Affairs Office in West Sumatra, including limited funds, inadequate reference modules, and a shortage of certified facilitators. These challenges have been addressed through budget proposals, the use of existing ministry modules, and facilitator training. However, implementation remains suboptimal due to limited guidance time, inadequate material coverage, short session durations, basic teaching methods, and the absence of technical experts. These factors may contribute to the continued increase in divorce cases observed in the region.